Energy contributions and greenhouse gas emissions in pepper (Capsicum annuum L.) cultivation with plastic mulch - Quimis-Guerrido, Byron Leonardo; Shkiliova, Liudmyla; Zambrano-Arteaga, Ramón Ignacio; Diomedes Guerrero-Arboleda, Benito; Sánchez Moreira, Jaime David; Ramírez Castro, Adolfo Emilio (Revista Ceres, 2023)
The objective of this work was to determine the use and efficiency of energy and to quantify the greenhouse gas (GHG) emissions, per hectare, for the cultivation of pepper, Capsicum anuum L., hybrid MIRELLA F1, using plastic mulch in the open-field. The assays were performed in a farm of Puerto La Boca (1° 20’ 51” S and 80° 43’ 51” W), the precinct of the Puerto Cayo parish of Jipijapa Municipality, Manabí province, Ecuador. The data was collected through field research, between March and September 2021, under observation and timing techniques. There was evidence of energy consumption and production (in the form of pepper berries) of 18,442.29 and 27,702.74 MJ ha-1, respectively, and a total GHG emission of 3,058.90 kg CO2-eq ha-1. The energy efficiency was determined at 1.50, the energy productivity 1.88 kg MJ-1, the specific energy 0.53 MJ kg-1, and the net energy 8,858.46 MJ ha-1. The quotas of direct and indirect energies were calculated at 9,513.15 and 8,929.15 MJ ha-1, respectively, and the proportion of renewable and non-renewable energies at 12,994.03 and 5,448.27 MJ ha-1, respectively. The GHG index per kg of MIRELLA F1 pepper yield was 0.088.